2012
DOI: 10.5194/bg-9-1519-2012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phytoplankton community structure in the South China Sea in response to the East Asian aerosol input

Abstract: Abstract. Recent studies have demonstrated atmospheric deposition as an important source of bioreactive compounds to the ocean. The South China Sea (SCS), where aerosol loading is among the highest in the world, however, is poorly studied, particularly on the in situ response of phytoplankton community structures to atmospheric deposition. By conducting a series of microcosm bioassays at different hydrographical locations and simulating different aerosol event scales, we observed both positive and nega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
69
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 82 publications
14
69
0
Order By: Relevance
“…An increase of the overall phytoplankton carbon biomass was also observed, but this effect was less pronounced (1.5-fold). The positive response of phytoplankton to dust addition is largely in accordance with many previous microcosm and mesocosm experiments performed in oligotrophic low nutrients low chlorophyll (LNLC) sites, such as in the east ( ; Tsagaraki et al, in review) and west Mediterranean basins (Bonnet et al, 2005;Lekunberri et al, 2010;Romero et al, 2011;Ridame et al, 2014), in the Atlantic Ocean (Marañón et al, 2010) and in South China Sea (Guo et al, 2012). Besides the single-addition experiment, additional mesocosm containers were subjected to three consecutive inoculations with smaller amounts of Saharan dust (RA treatment) in order to better simulate the recurrent pattern of Saharan dust events in the eastern Mediterranean, where continuing dust deposition events may occur over a period of several days (Meloni et al, 2008;Gaetani and Pasqui, 2014;Vincent et al, 2016).…”
Section: Discussion the Effect Of Dust Addition Treatments On Phytoplsupporting
confidence: 69%
See 2 more Smart Citations
“…An increase of the overall phytoplankton carbon biomass was also observed, but this effect was less pronounced (1.5-fold). The positive response of phytoplankton to dust addition is largely in accordance with many previous microcosm and mesocosm experiments performed in oligotrophic low nutrients low chlorophyll (LNLC) sites, such as in the east ( ; Tsagaraki et al, in review) and west Mediterranean basins (Bonnet et al, 2005;Lekunberri et al, 2010;Romero et al, 2011;Ridame et al, 2014), in the Atlantic Ocean (Marañón et al, 2010) and in South China Sea (Guo et al, 2012). Besides the single-addition experiment, additional mesocosm containers were subjected to three consecutive inoculations with smaller amounts of Saharan dust (RA treatment) in order to better simulate the recurrent pattern of Saharan dust events in the eastern Mediterranean, where continuing dust deposition events may occur over a period of several days (Meloni et al, 2008;Gaetani and Pasqui, 2014;Vincent et al, 2016).…”
Section: Discussion the Effect Of Dust Addition Treatments On Phytoplsupporting
confidence: 69%
“…Microcosm and mesocosm experimental studies performed mostly in NW Mediterranean and the Atlantic Ocean demonstrated that inputs of dust and aerosols enhanced primary production (Ridame and Guieu, 2002;Bonnet et al, 2005;Marañón et al, 2010) and phytoplankton biomass (Guo et al, 2012;Giovagnetti et al, 2013), as well as bacterial abundance Marañón et al, 2010) and/or bacterial respiration (Pulido-Villena et al, 2014). However, phytoplankton and heterotrophic prokaryotes did not show a consistently positive response, in terms of biomass and production, to dust additions nor presented similar patterns among all experiments.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Synechococcus abundance was lowest in the "high" aerosol treatment ( Figure 1J). These negative responses could be due to competition (i.e., if picoplankton were outcompeted due to aerosol fertilization of other species in the community), or toxicity from trace metals Guo et al, 2012). The PCA suggests that the responses are likely a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been evaluated through incubation experiments, in situ experiments and the use of satellite observational data (Banerjee and Kumar, 2015;Guo et al, 2012;Liu et al, 2013;Shi et al, 2012;Tan and Wang, 2014). However, the process is dynamic due to the worldwide changing emissions of NO x and NH 3 in the last few decades.…”
Section: Introductionmentioning
confidence: 99%